AN ARCHITECTURE FOR INTELLIGENT DIAGNOSIS OF DIABETIC TYPES AND COMPLICATIONS BASED ON SYSMPTOMS - THANGARASU, GUNASEKAR (2017)
The clinical database has an extensive amount of information. The database usually contains doctor's counsel, results of clinical examinations, patient history and clinical symptoms of various types of biochemical data that physician considers in order to grasp a final diagnostic decision.